Hospital admissions through the National Health System (SUS) in the east of south expanded health region of Minas Gerais, Brazil, between 2014 and 2018 - Soares, Renan Repolês; Henriques, Bruno David; Sediyama, Catarina Maria Nogueira de Oliveira; Lima, Luciana Moreira (Ciência e Natura, 2022)
Hospitalizations occur electively in cases with no imminent risk to life or in cases of urgency and emergency, which demand immediate medical assistance. In a Health Region, these hospitalizations are conducted in reference hospitals. This study aimed to analyse hospital admissions in the Eastern South Region of Minas Gerais, by comparing the number of urgency and emergency admissions with elective procedures admissions and with the number of urgency admissions with sensitive to primary care conditions (CSAP). This longitudinal-retrospective-descriptive study was conducted with Hospital Information System (SIH) data relative to the 2014-2018 interval. Altogether, there were registered 129,524 hospitalizations, with 17,546 (13.55%) being elective admissions and 111,978 (86.45%) urgency procedures. Of the urgency hospitalizations total, 20,108 (17.95%) were CASP hospitalizations. The frequency of urgency hospitalization was six times higher than the elective hospitalization one, and even SPCC emergency admissions exceeded the elective hospitalizations offer.